Job Satisfaction Determinants in Indonesian Financial Industry: Insights from Online Employee Reviews - Faza, Nadif Muhammad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Employee job satisfaction plays a crucial role in reducing turnover, a persistent challenge in Indonesia’s financial industry. While prior research has primarily relied on survey-based methods. research that leverages online employee reviews within this context remains limited. This study addresses this gap by adopting a sequential mixed-methods approach to examine employee-perceived work experiences and their impact on job satisfaction. Drawing on 6,999 employee reviews posted on Glassdoor (2015-2025), the analysis integrates LDA topic modeling with OLS path analysis to examine determinants of job satisfaction. The findings identify seven key topics, including management, career development, job design, work environment, organizational culture, job demands, and compensation. Notably, management is the only topic with a significant positive effect on job satisfaction, highlighting the importance of supportive and inclusive leadership practices. In contrast, the remaining topics exhibit significant negative effects, with job demands emerging as the strongest driver of dissatisfaction, reflected by concerns about excessive workloads and long working hours. Overall, the results indicate that negative work experiences exert a stronger effect on job satisfaction than positive ones. This study contributes to the literature by demonstrating the value of online employee reviews as a reliable data source and by providing data-driven HRM strategies to improve employee satisfaction and retention.